2009
DOI: 10.1021/ol9015942
|View full text |Cite
|
Sign up to set email alerts
|

Tetradehydrodinaphtho[10]annulene: A Hitherto Unknown Dehydroannulene and a Viable Precursor to Stable Zethrene Derivatives

Abstract: The synthesis and structural characterization of hitherto unknown tetradehydrodinaphtho[10]annulene, a hydrocarbon whose synthesis had been attempted four decades ago, was achieved for the first time. Moreover, the dinaphtho[10]annulene was transformed smoothly into stable zethrene derivatives substituted at its 7,14-positions, showing that it serves as a good reservoir of zethrene derivatives. Optical and electrochemical properties of a disubstituted zethrene derivative are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…In 2009, Umeda's group reported the successful synthesis and isolation of the tetradehydrodinaphtho [10]annulene (9) and its subsequent transannular cyclization triggered by addition of iodine to give the 7,14-diiodozethrene 24 (Scheme 4). 9 Compound 24 can serve as a key intermediate for the synthesis of 7,14-substituted zethrene derivatives via transition metal catalyzed cross coupling reactions. In 2010, Wu's group discovered that Pd-catalyzed cyclodimerization of 1-iodo-8-ethynylnaphthalene derivative 26 gave the bay-substituted zethrenes 27 in good yields.…”
Section: Renaissance Of Zethrene Chemistrymentioning
confidence: 99%
“…In 2009, Umeda's group reported the successful synthesis and isolation of the tetradehydrodinaphtho [10]annulene (9) and its subsequent transannular cyclization triggered by addition of iodine to give the 7,14-diiodozethrene 24 (Scheme 4). 9 Compound 24 can serve as a key intermediate for the synthesis of 7,14-substituted zethrene derivatives via transition metal catalyzed cross coupling reactions. In 2010, Wu's group discovered that Pd-catalyzed cyclodimerization of 1-iodo-8-ethynylnaphthalene derivative 26 gave the bay-substituted zethrenes 27 in good yields.…”
Section: Renaissance Of Zethrene Chemistrymentioning
confidence: 99%
“…Though attempts to prepare 1 by coupling of 1,8-diethynylnaphthalene (5b) [5,6,10] and 1,8-diiodonaphthalene (6) or self-coupling of 1-ethynyl-8-iodonaphthalene (4b) [5] under the standard Sonogashira-Hagihara reaction conditions failed, the cross-coupling of 5c and 6 with in situ deprotection by 1 equiv of aqueous NaOH [11] gave 1 in 22 % yield [3], together with a small amount (4 %) of monoiodozethrene 2b [6]. When the reaction was undertaken without NaOH, the yield of 1 dropped to 6 % and mono-coupling product 7b was obtained as the major product (33 %).…”
Section: Synthesis Of Tetradehydrodinaphtho[10]annulenementioning
confidence: 99%
“…Recently, we succeeded in the first synthesis of the long-sought tetradehydrodinaphtho [10]annulene (1), which had eluded isolation since attempts initiated during the late 1960s, utilizing Pd-catalyzed cross-coupling reaction as the pivotal step [3]. Moreover, 1 was readily transformed via transannular cyclization into 7,14-diiodozethrene (2c), which in turn was converted to bis(phenylethynyl) derivative 2d.…”
Section: Introductionmentioning
confidence: 99%
“…The proximate triple bonds in such precursors make them reactive towards heating, light irradiation, or in the presence of electrophiles, and the intramolecular transannular cyclization usually takes place simultaneously to afford the corresponding zethrene and heptazethrene derivatives. Tobe et al reported that the precursor tetradehydrodinaphtho [10]annulene 6 can be isolated and converted to the 7,14-diodozethrene 7 by reaction with iodine [17]. Our group reported a one-pot synthesis of the zethrene diimide 9 by Stille coupling/transannular cyclization from compound 8, and the reaction was supposed to go through a reactive tetradehydrodinaphtho [10]annulene intermediate [18].…”
Section: Synthesismentioning
confidence: 95%
“…Currently, the functionalizations of zethrene are achieved at 7,14-positions (bay region) and 3,4,10,11-positions (naphthalene unit) to afford 7,14-disubstituted zethrenes 16 [17,20] and zethrene diimides 9, 18a-d [18,20] (Fig. 3).…”
Section: Tunable Ground States and Physical Properties Zethrene And Imentioning
confidence: 99%